2023
DOI: 10.3390/v15040839
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Dengue Virus Peptide DV2 Inhibits Zika Virus Both In Vitro and In Vivo

Abstract: The C-terminal portion of the E protein, known as stem, is conserved among flaviviruses and is an important target to peptide-based antiviral strategies. Since the dengue (DENV) and Zika (ZIKV) viruses share sequences in the stem region, in this study we evaluated the cross-inhibition of ZIKV by the stem-based DV2 peptide (419–447), which was previously described to inhibit all DENV serotypes. Thus, the anti-ZIKV effects induced by treatments with the DV2 peptide were tested in both in vitro and in vivo condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In its active form, this serine protease complexes with the NS2B cofactor (NS2B-NS3) and is essential for cleaving the polyprotein and releasing other essential proteins for viral replication. Due to its essentiality and mechanistic conservation, the NS3 pro remains an interesting antiviral target , for development of panflavivirus bioactive compounds. , Until now, NS3 pro inhibitors have mainly focused on peptides or peptidomimetic inhibitors. However, they have poor in vivo bioavailability and high molecular weight. Nonpeptide active compounds have increased bioavailability but remain to be further developed. The combination of a diverse set of computational techniques can be useful to identify novel nonpeptide hit compounds. Furthermore, previous computational approaches helped in the development of viral protease inhibitors, such as boceprevir and ritonavir, and recently both SARS-CoV-2 main protease (M pro ) inhibitors, nirmatrelvir and ensitrelvir …”
Section: Introductionmentioning
confidence: 99%
“…In its active form, this serine protease complexes with the NS2B cofactor (NS2B-NS3) and is essential for cleaving the polyprotein and releasing other essential proteins for viral replication. Due to its essentiality and mechanistic conservation, the NS3 pro remains an interesting antiviral target , for development of panflavivirus bioactive compounds. , Until now, NS3 pro inhibitors have mainly focused on peptides or peptidomimetic inhibitors. However, they have poor in vivo bioavailability and high molecular weight. Nonpeptide active compounds have increased bioavailability but remain to be further developed. The combination of a diverse set of computational techniques can be useful to identify novel nonpeptide hit compounds. Furthermore, previous computational approaches helped in the development of viral protease inhibitors, such as boceprevir and ritonavir, and recently both SARS-CoV-2 main protease (M pro ) inhibitors, nirmatrelvir and ensitrelvir …”
Section: Introductionmentioning
confidence: 99%
“…Overall, the findings of this work indicated that the DV2 peptide could be a promising agent for treating ZIKV infections, possibly preventing or reducing neurological impairment in neonates linked to infection in pregnant women. Moreover, this work provided indications for developing anti-flavivirus drugs from synthetic stem-based peptides [ 8 ].…”
mentioning
confidence: 99%